Entrepreneurial orientation for small and medium travel agencies in Malaysia - Mohd Kamal, Saiful Bahri; Zawawi, Dahlia; Abdullah, Dahlan (Elsevier, 2016)
New tourism trend and products are fast emerging within travel industry. Nevertheless, small and medium travel agencies are unable to exploit these new business opportunities and venture into new travel product. The purpose of this conceptual paper is to propose a study that brings out an exploratory research which intends to evaluate and assess the entrepreneurs’ new product development capabilities as well as market responsiveness, paying attention on through the implementation of cooperation. The establishment of different intangible resources gained through cooperation could boost entrepreneurial capabilities (new product development and market responsiveness) that will lead to the provision of competitiveness and growth in performance. This information is regarded as valuable resource that could be used by travel agency entrepreneurs as well as related agencies to understand the enhanced resources and capabilities needed to direct them towards business growth and positive development.